British Society of Gastroenterology and UK-PSC guidelines for the diagnosis and management of primary sclerosing cholangitis. Issue 8 (1st June 2019) - Chapman, Michael Huw; Thorburn, Douglas; Hirschfield, Gideon M; Webster, George G J; Rushbrook, Simon M; Alexander, Graeme; Collier, Jane; Dyson, Jessica K; Jones, David EJ; Patanwala, Imran; Thain, Collette; Walmsley, Martine; et al.
Abstract : These guidelines on the management of primary sclerosing cholangitis (PSC) were commissioned by the British Society of Gastroenterology liver section. The guideline writing committee included medical representatives from hepatology and gastroenterology groups as well as patient representatives from PSC Support. The guidelines aim to support general physicians, gastroenterologists and surgeons in managing adults with PSC or those presenting with similar cholangiopathies which may mimic PSC, such as IgG4 sclerosing cholangitis. It also acts as a reference for patients with PSC to help them understand their own management. Quality of evidence is presented using the AGREE II format. Guidance is meant to be used as a reference rather than for rigid protocol-based care as we understand that management of patients often requires individual patient-centred considerations.